Soybean seed proteome rebalancing - Herman, Eliot M. (Frontiers in Plant Science, 2014)
The soybean seed’s protein content and composition are regulated by both genetics and physiology. Overt seed protein content is specified by the genotype’s genetic framework and is selectable as a breeding trait. Within the genotype-specified protein content phenotype soybeans have the capacity to rebalance protein composition to create differing proteomes. Soybeans possess a relatively standardized proteome, but mutation or targeted engineering can induce large-scale proteome rebalancing. Proteome rebalancing shows that the output traits of seed content and composition result from two major types of regulation: genotype and post-transcriptional control of the proteome composition. Understanding the underlying mechanisms that specifies the seed proteome can enable engineering new phenotypes for the production of a high-quality plant protein source for food, feed, and industrial proteins.